Psycholinguistic, ethno-sociocultural aspects as basis of intercultural communication - Mavlonova Oybarchin Sheraliyevna (Zien Journals, 2022)
This article describes in detail the psycholinguistic, ethno-sociocultural aspects, ethnosociocultural concepts and the basis of intercultural communication.
Keywords: psycholinguistic; ethno-sociocultural; intercultural communication; synthesis